Spatiotemporal pattern of COVID-19 and government response in South Korea (as of May 31, 2020) - Sun Kim; Marcia C. Castro (International Journal of Infectious Diseases, 2020)
Objectives: The aim of this study was to assess how coronavirus disease 2019 (COVID-19) clustered across districts in South Korea and to assess whether the pattern and duration of clusters changed following the country's containment strategy. Methods: A spatiotemporal analysis of COVID-19 daily confirmed cases by 250 districts in South Korea from January 20 to May 31, 2020, obtained from the Korea Centers for Disease Control and Prevention and each provincial website, was conducted. The global Moran's I statistic was used for spatial autocorrelation analysis, and the retrospective space-time scan statistic was used to analyze spatiotemporal clusters of COVID-19. Results: The geographical distribution showed strong spatial autocorrelation, with a global Moran's I coefficient of 0.784 (p = 0.0001). Twelve statistically significant spatiotemporal clusters were identified by space–time scan statistic using a discrete Poisson model. The spatial pattern of clusters changed and the duration of clusters became shorter over time. Conclusions: The results indicate that South Korea's containment strategy for COVID-19 was highly effective in both early detection and mitigation, with recent clusters being small in size and duration. Lessons from South Korea should spark a discussion on epidemic response.